2003
DOI: 10.4049/jimmunol.170.8.4155
|View full text |Cite
|
Sign up to set email alerts
|

APCs Present Aβk-Derived Peptides That Are Autoantigenic to Type B T Cells

Abstract: Type B T cells recognize peptide provided exogenously but are ignorant of the same epitope derived from intracellular processing. In this study, we demonstrate the existence of type B T cells to an abundant autologous peptide derived from processing of the I-Ak β-chain. T cell hybridomas raised against this peptide fail to recognize syngeneic APC despite abundant presentation of the naturally processed epitope but react in a dose-dependent manner to exogenous peptide. Moreover, these hybridomas respond to Aβk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
(27 reference statements)
3
25
0
Order By: Relevance
“…In experiments in progress we are reporting on the content and features of peptides bound to I-A k in T1.A k and T2.A k examined by tandem electrospray mass spectrometry. In our previous analysis of one peptide family presented by I-A k (derived from the I-A k ␤-chain), we found reduced abundance of this high affinity peptide family on T2.A k relative to T1.A k (26). The biochemical results were confirmed by functional assays.…”
Section: Resultssupporting
confidence: 49%
“…In experiments in progress we are reporting on the content and features of peptides bound to I-A k in T1.A k and T2.A k examined by tandem electrospray mass spectrometry. In our previous analysis of one peptide family presented by I-A k (derived from the I-A k ␤-chain), we found reduced abundance of this high affinity peptide family on T2.A k relative to T1.A k (26). The biochemical results were confirmed by functional assays.…”
Section: Resultssupporting
confidence: 49%
“…The generation of the MOG-specific T cell hybridoma 204.62 was performed according to standard protocol (31). Briefly, B6 mice were immunized via footpad injection of 10 nM of MOG emulsified in CFA (Difco, Detroit, MI).…”
Section: Antigen Presentation Assaymentioning
confidence: 99%
“…A total of 5×10 5 APCs were cultured with 5×10 4 hybridoma cells with antigen overnight at 37C. Proliferation of CTLL-2 was measured after addition of supernatant by [ 3 H]thymidine incorporation as described (31). EC 50 was calculated by constructing a dose-response curve for each population of APCs, using the concentration of rMOG providing half-maximal IL-2 response by the hybridoma 204.62.…”
Section: Antigen Presentation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was first observed in studies of a so-called cryptic epitope (4) but has since been observed with regard to a variety of epitopes and MHC molecules and appears to be a general feature of class II MHC-peptide interaction (5)(6)(7)(8). Selfreactive type B T cells escape negative selection under conditions in which type A T cells are deleted in the thymus, suggesting that they may play a role in autoimmunity (9,10). Furthermore, a subset of type B T cells recognize peptides as short as seven residues; we speculate that these may be involved in host defense, responding to short peptides of microbial origin (11).…”
mentioning
confidence: 99%